The Evolution of Teacher Education and Professional Development in Japan: Education as a Craft - Badawi, Ghina; Badawi, Habib (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This study examines Japan's teacher professional development model, emphasizing teaching as a “craft” and its integration within an extensive in-service education system. It highlights the postwar evolution of teacher training in Japan, where universities play a pivotal role in preparing educators through an integrated system. The research explores assumptions about in-service education, detailing programs such as internal professional development, government-sponsored initiatives, and teacher-led networks. Unique to Japan is the peer-based model fostering collaboration among colleagues, enhancing “craft knowledge” through reflective practice and continuous training. This approach intertwines past professional practices with present applications, preparing for future teaching needs. The historical influence of the postwar American occupation shaped Japan's distinctive teacher education model, combining in-service and graduate-level programs to develop specialized competencies. The study also addresses critical issues, including teachers' intensified working hours, limited autonomy, and the stress linked to ongoing professional development. It underscores how teaching as a craft deeply embeds itself in Japanese teachers' lives, particularly at the elementary level, and identifies six themes influencing their development. Through a descriptive and analytical methodology supported by historical documents, empirical studies, and existing literature, the paper presents a comprehensive overview of Japan's professional development strategies, offering insights into its educational culture. These strategies, based on collaboration and reflective practice, serve as a valuable model for academic communities in Lebanon and the Arab world, highlighting the integration of traditional teaching concepts with modern professional training.